Structurally-dynamic analysis of indicators of trade and economic relations of Russia and the countries GCC in 2005-2009 (Путеводитель предпринимателя)
In article the structurally-dynamic analysis ofindicators of trade and economic relations of Russia and the countries GCC in 2005—2009 is carried out ascertained that trade and economic cooperation GCC and Russia yet has not reached so-called mature age for which the settled structure of export and import is characteristic. At the same time, the Russian Federation possesses real possibilities to keep the presence at the Arabian world.